1985
DOI: 10.18474/0749-8004-20.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Blow Fly (Diptera: Calliphoridae) Succession on Carrion in Northern Mississippi

Abstract: Blow fly succession on carrion was investigated in Lafayette County, Mississippi. Phaenicia caeruleiviridis, Phormia regina and Cochliomyia macellaria were dominant species from April through September and Cynomyopsis cadaverina, P. regina and Calliphora livida dominated during the cooler months (October through March). Although both fish and mammalian carrion were used, and baits were placed in different habitats, no differences between types of bait and types of habitat were observed. The use of P. caeruleiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 0 publications
4
25
0
Order By: Relevance
“…We found that carcass decomposition occurred most rapidly in warm sunlit conditions, corroborating Goddard and Lago (1985) who noted that decomposition occurred much faster on warm sunny days than on cooler days, and Shean et al (1993) who reported that an exposed (i.e., sunlit) pig was consumed at a much faster rate than a shaded one. Thus under these warm sunlit conditions, where the suitability of carcass substrates as feeding and oviposition sites was of shorter duration, we recorded the shortest adult visitation periods; 72 h for L. coeruleiviridis, and 120 h for P. regina (Fig.…”
Section: Adult Visits and Carcass Decompositionsupporting
confidence: 88%
See 4 more Smart Citations
“…We found that carcass decomposition occurred most rapidly in warm sunlit conditions, corroborating Goddard and Lago (1985) who noted that decomposition occurred much faster on warm sunny days than on cooler days, and Shean et al (1993) who reported that an exposed (i.e., sunlit) pig was consumed at a much faster rate than a shaded one. Thus under these warm sunlit conditions, where the suitability of carcass substrates as feeding and oviposition sites was of shorter duration, we recorded the shortest adult visitation periods; 72 h for L. coeruleiviridis, and 120 h for P. regina (Fig.…”
Section: Adult Visits and Carcass Decompositionsupporting
confidence: 88%
“…We found that L. coeruleiviridis arrived at carcasses early, but their numbers diminished over time, being supplanted by P. regina adults. The same pattern of relative numbers for these two species over time in the decomposition process was observed by (Goddard and Lago 1985).…”
Section: Adult Visits and Carcass Decompositionsupporting
confidence: 72%
See 3 more Smart Citations